A prospective comparative study of functional outcome following platelet-rich plasma versus Triamcinolone injection for treatment of early primary osteoarthritis knee - Trivedi, Nirav; Patel, Tirth; Tripathi, Shyam (International Journal of Research in Orthopaedics, 2025)
Background: Osteoarthritis in knee joints is very common in developing countries in middle aged and elderly populations. Triamcinolone and platelet rich plasma (PRP) injections can increase the functional outcome and delayed need for surgical intervention in early primary osteoarthritis. This study is aimed to evaluate the functional outcome and the total time effect of the injection in the patients. Methods: This is a prospective comparative study which included 100 patients out of which 50 were given triamcinolone injection and 50 were given PRP injection. Patients were selected as per grade 1 and grade 2 according to Kellgren Lawrence grade. Results: Among 100 patients 71 were male and 29 were female with most common age group being 51 to 60 years followed by 41 to 50 years. Out of 100 patients grade 1 consisted of 69 patients and grade 2 consisted of 31 patients. The triamcinolone group had immediate better functional outcome for an average of 3-6 months whereas PRP injections had better outcome for an average of 6-12 months. Conclusions: Patients injected with triamcinolone had an immediate better functional outcome for an average of 3-6 months whereas PRP injections had a delayed betterment of functional outcome which lasted for an average of 6-12 months.